Efektivitas Model Pembelajaran STAD (Student Team Achievement Division) terhadap Kemampuan Pemecahan Masalah Matematika Siswa SMA: The Effectiveness of the STAD (Student Team Achievement Division) Learning Model on the Mathematical Problem-Solving Ability of Senior High School Students - Aminah, Aminah (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Mathematical problem-solving ability is a crucial competency that senior high school students must master, yet many students still face difficulties. This study aims to analyze the effectiveness of the STAD (Student Team Achievement Division) learning model on the mathematical problem-solving ability of senior high school students. The study employed a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 64 eleventh-grade students, divided into an experimental group (n=32) that implemented the STAD model and a control group (n=32) that used conventional learning. The research instrument was a validated mathematical problem-solving ability test. The results showed that the experimental group experienced a significant increase in problem-solving ability compared to the control group (p < 0.05), with an effect size of 0.78. This finding indicates that the STAD learning model is effective in enhancing the mathematical problem-solving ability of senior high school students, particularly in the aspects of understanding the problem and planning a solution strategy. The implication of this research offers an alternative solution for mathematics teachers to implement the STAD type of cooperative learning to improve students' mathematical problem-solving abilities.